Authentication of Wild Boar Meat in Meatball Formulation Using Differential Scanning Calorimetry and Chemometrics - Guntarti, Any; Rohman, Abdul; Martono, Sudibyo; Yuswanto, Agustinus (Journal of Food and Pharmaceutical Sciences, 2017)
Bakso or meatball is one of the Indonesian favorite foods, commonly made from beef. This food is quite popular among Indonesian societies. Due to the high price of beef, unethical producers may adulterate beef with wild boar meat (WBM). In this study, the potential use of differential scanning calorimetry (DSC) combined with multivariate calibration was used to verify adulteration of WBM in meatball formulation. Oil extracted from WBM is characterized by significantly different cooling and heating DSC thermal profiles. The change of characteristic exothermic and endothermic event in oil with increasing crystallization, melting enthalpy and developing both process over a narrower temperature range is investigated. In this research, we developed DSC and multivariate calibration of Partial Least Square (PLS) calibration to analyze WBM in beef meatball. Meanwhile, the chemometrics of Principle Componen Analysis (PCA) is used to classify WBM and beef in the meatball. The validation model using crystalization profiles yield the coefficient of determination (R2) of 0.999 for the correlation between actual value of WBM (x-axis) and DSC predicted value (y-axis) with equation of y= 0.9999 x + 0.0027, root mean square error of cross validation (RMSECV) of 0.380%, and root mean square error of prediction (RMSEP) of 0.203%. PCA is successfully used for classification of WBM in beef meatball. DSC in combination with PLS and PCA can be an alternative technique for analysis of WBM in meatball.Key words: Differential scanning calorimetry, Wild bear meat, Crystallization profile, Melting profile, Partial least square.